Analisis GDP Sebagai Jalan Keluar dari Situasi Middle Income Trap - Marsandhi Evan Dino Pardede; Sunu Kun Aziz (Politeknik Statistika STIS, 2022)
Middle Income Trap is a situation when a country manages to get out of the low income level to the middle income level, but the country can't pass to the high income class. Economic stagnation makes it difficult for the country to increase its income which causes the country to enter into a Middle Income Trap situation. The method used is structural equation regression with 2SLS estimation method. The purpose of this study is to determine the factors that significantly affect the income of the middle class country, both directly and in total and to find out whether the effect of the economic slowdown significantly affects the difficulty of middle income class countries getting out of the Middle Income Trap situation. The results obtained show that the variables that have a significant direct impact on GDP are investment and HDI. For the total impact, the variables that significantly affect GDP are FDI outflow, exports, CPI, exchange rate, unemployment rate and government effectiveness. From the results of the analysis, it is found that the slowdown in economic income has not been significant in middle-income class countries.